Oriented and annealed poly(lactic acid) films and their performance in flexible printed and hybrid electronics. (October 2021) - Luoma, Enni; Välimäki, Marja; Rokkonen, Teijo; Sääskilahti, Hannu; Ollila, Jyrki; Rekilä, Jari; Immonen, Kirsi
Flexible and hybrid electronics (FHE) are widely utilized from wearable to automotive applications. Instead of commonly used poly(ethylene terephthalate) (PET) film, bio-based and biodegradable polymer, poly(lactic acid) (PLA), is a most promising novel substrate alternative for FHE. From the point of heat curable conductive inks, the poor heat resistance and inherent brittleness are the major drawbacks of PLA. By increasing the PLA film crystallinity through orientation and annealing, its properties can be improved. Two commercial grades, standard PLA (PLA) and a high heat PLA (hhPLA), plus one stereocomplex PLA (scPLA) blend were used to compare PLA performance with different optical purities and crystallinity for printed FHE. Machine direction orientation (MDO), biaxial orientation (BO) and annealing improved the stability of the laboratory and pilot scale manufactured PLA films. MDO was more effective in improving stiffness and strength while BO resulted in more ductile behaviour. In hhPLA the crystallinity increased from 0% to 50% improving tensile strength by 83%, tensile modulus by 52% and strain at break from 3.7% to 114% with 3 × 3 BO and annealing. The scPLA blend contained homo- and stereocomplex crystallites and a double melting peak behaviour provided higher temperature stability through final melting at 220°C. Its optical transparency reached 95%, remaining high up to 250 nm wavelength. In roll-to-roll printing, the PLA and hhPLA films were dried at 100°C prior the printing and this decreased the MD elongation from 2.55% and 0.27% to 0.00–0.05%. The sheet resistance of printed silver was <40 mΩ/sq with additional drying for printed and hybrid integrated light-emitting diode (LED) foils. Printed LED foils on PLA had dimensional and electrical performance comparable to PET, even though lower drying temperatures were used.